Pengaruh Pelatihan Dan Kompetensi Sumber Daya Manusia Terhadap Produktivitas Kerja Karyawan Pada Pt Wilmar Nabati Kota Medan - Wijaya, Angieta Ahsana; Siregar, Onan Marakali (Peneliti.net, 2025)
Human resources (HR) is a very crucial factor in achieving company goals and development. The development and goals of the company can be achieved if the company succeeds in increasing employee productivity, one of which is influenced by several factors, namely the existence of training and the level of competence of human resources. This study aims to analyze how training and human resource competencies affect employee productivity at PT Wilmar Nabati Medan City. The influence between training and human resource competencies will be analyzed partially and simultaneously on employee work productivity. The form of research used in this research is quantitative research with an associative approach. The population in this study were all employees at PT Wilmar Nabati Medan City, totaling 163 people and a sample size of 62 respondents with sampling techniques using simple random sampling. The primary data used in this study were obtained by distributing questionnaires directly while secondary data were obtained through literature studies. The data analysis methods used are instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that training and human resource competencies had a positive and significant effect both partially and simultaneously on employee productivity at PT Wilmar Nabati Medan City. The correlation coefficient (R) value is 0.911, which means that there is a relationship between the Training (X1) and Human Resource Competencies (X2) variables on Employee Work Productivity (Y) of 91.1% so that the relationship between variables can be categorized as very close. The Adjusted R Square value of 0.824 or the coefficient of determination shows that the Training (X1) and Human Resource Competencies (X2) variables on Employee Work Productivity (Y) are 82.4% while the remaining 17.8% are influenced by other variables outside of the variables studied.